The Comparison Implementation Of Reinventing Policy 2015 AND Tax Amnesty 2016 (Case Study At Kendari Tax Office) - Prabowo, Dibyo; Herwanti, Titiek; Asmony, Thatok (Advances in Social Sciences Research Journal, 2018)
Indonesia in the last two years has implemented the policy of tax pardon in a row that is reinventing policy in 2015 and tax amnesty in 2016. The tax amnesty policy implemented in 2016 is recognized as the most successful tax forgiveness success in the world. This study aims to determine the difference of policy implementation of reinventing policy pardon policy in 2015 and tax amnesty in 2016. The study was conducted qualitatively by using exploratory case study with the aim of knowing the difference of the implementation process of Tax Amnesty policy in 2016 and the policy reinventing policy in 2015. This research was conducted in Primary Service Office (KPP) Pratama Kendari which participate in implementing tax amnesty policy 2016 and reinventing policy policy 2015. The results show there are differences in the implementation of both policies among others from the basic aspects of policy law, the scope of policy and the ease of policy implementation.